A Frailty Index Identifies Patients at High Risk of Mortality after Tracheostomy. (April 2014) - Johnson, Matthew S.; Bailey, Travis L.; Schmid, Kendra K.; Lydiatt, William M.; Johanning, Jason M.
Objective: To evaluate the utility of a modified frailty index as an indicator of postoperative mortality in patients undergoing tracheostomy. Study Design: Case series with chart review. Setting: Tertiary care veterans hospital. Subjects and Methods: A chart review was conducted of consecutive tracheostomies performed between April 2007 and September 2012. A modified frailty index consisting of 11 items based on the Revised Minimum Data Set Mortality Rating Index (MMRI-R) was retrospectively applied using the patient's status immediately prior to tracheostomy. The resultant 6-month calculated mortality risk was compared with both the Veterans Health Administration Surgical Quality Improvement Program's (VASQIP) 30-day calculated mortality and actual mortality. Results: One hundred consecutive tracheostomies were analyzed. No patients were excluded. Sixty-nine patients died within the study period, with 1-, 6-, and 12-month mortality rates of 25%, 43%, and 59%, respectively. The average calculated 6-month mortality risk using the modified frailty index was 40.5% for nonsurvivors compared with 25.4% for survivors ( P = .001). Both the VASQIP calculator and modified frailty index differentiated mortality risks between patients without head and neck cancer who survived less than 6 months versus those who survived longer than 6 months ( P = .006 and .01). However, neither the VASQIP nor the modified frailty index differentiated mortality risks for head and neck cancer patients who survived less than 6 months versus greater than 6 months ( P = .94 and .26). Conclusion: A modified frailty index identifies patients without head and neck cancer at high risk of postoperative mortality after tracheostomy.